Evaluation of a Loop-Mediated Isothermal Amplification Method as a Tool for Diagnosis of Infection by the Zoonotic Simian Malaria Parasite Plasmodium knowlesi - Iseki, Hiroshi (American Society for Microbiology (ASM), 2010)
Loop-mediated isothermal amplification (LAMP) is a novel method that rapidly amplifies target DNA with high specificity under isothermal conditions. It has been applied as a diagnostic tool for several infectious diseases, including viral, bacterial, and parasitic diseases. In the present study, we developed a LAMP method for the molecular diagnosis of Plasmodium knowlesi infection (PkLAMP) and evaluated its sensitivity, specificity, and clinical applicability. We designed three sets of PkLAMP primers for the species-specific β-tubulin gene. The primer sets for PkLAMP specifically amplified the autologous DNA extracts of P. knowlesi, and the sensitivity of the test was 100-fold that of single-PCR assay. These results indicate that our PkLAMP method can be used to efficiently distinguish between P. knowlesi and other malaria parasites. To evaluate the feasibility of using in vivo materials, comparisons of PkLAMP and the conventional nested PCR (nPCR) method and microscopic examination were made with blood samples from two experimentally infected monkeys. These studies showed that P. knowlesi infection can be identified much earlier with PkLAMP than with nPCR and microscopy. Moreover, the detection performance of PkLAMP using whole blood as the template was identical to that of PkLAMP when genomic DNA extracts were used. These results suggest that the PkLAMP method is a promising tool for molecular diagnosis of P. knowlesi infection in areas of endemicity.